Addressing Cervical Stenosis and Uterine Fibroids in IVF: A Case Study on the Effectiveness of TMET - Shradha Ulhe; Namrata Choudhary; Akash More; Sudhanshu Dakre (Journal of Pharmacy and Bioallied Sciences)
This case study presents a 38-year-old female with a history of infertility complicated by severe cervical stenosis and intramural fibroids, which rendered traditional transcervical embryo transfer (ET) ineffective. After previously failed cycles of in vitro fertilization, the couple was advised for transmyometrial embryo transfer (TMET), an invasive technique that places the embryo straight into the lining of the endometrium rather than through the cervix. Full assessment showed appropriate hormone levels and normospermia excluding the presence of male factor infertility. The patient received ovarian stimulation, oocyte retrieval, and ET through TMET. After the procedure, progesterone supplementations were given to sustain the luteal phase. A beta hCG test returned a positive result after 2 weeks of the transfer confirming pregnancy. This case illustrates the effectiveness of TMET in avoiding the anatomical issues associated with conventional ET and reinforces the concept of the need for customized fertility care.